Um olhar sobre o estatuto da cidade enquanto instrumento de reforma urbana: um estudo sobre a elaboração e implementação do plano diretor em Caldas Novas - Paiva, Dirceu Lopes (2004)
This paper aims to analize the process of criation and implementation of the Director Plan in the city of Caldas Novas, according to the Federal Law 10.257 from July 10th ,2001, known as city document. To reach that objective, the process o f urbanization tíiat the country lived in the past forty years must be, as well as the social , economomical and spacial conditions experienced by the brazilian population in the same period. The literature turned to the urban matters in Brazil has its focus mainly in the big cities problems, but those problems are present in the médium and small cities, after all in those who show some partícularities , how a fast demographyc growth, among others. In this context, the city of Caldas Novas stands as reference for analyze that group of cities, with a high tax of demographyc growth, among other importants characteristics, like the exploration of the thermal waters and the fact o f being the greatest touristic center in the Central West. Caldas Novas, for having more than 20.000 inhabitants and for being considered as area of high touristic interest, characteristics that put it in the group of cities that are obligated to make or elaborate its Director Plan, the city had its own Plan created in the early 2000, becoming valid in august I5l , 2003. The qualitative research was used as method of study, working with documental research, using this way to find samples about the matters that act like basis to keep the proposals of the city document; and with interviews that were useful to analyze the perceptions, critics and informations of the agents of the process of creation of the plan and the people linked to the recent development of the country, beyond the writing of some papers, which informations weren’t in any other research. In the final considerations, the weak popular participation was showed, as an important contribution to the creation of the Director Plan, explicitating the democratic character, but with the absence of some important informations, after all those related to the cicie of thermal waters and other about the urban infrastructure. Another important matter was the implementation of the urban development council, that with only few months o f action, reached signifícant gains in favor of the coletive interests, specialy in those matters about the donations of public areas.